Maternal communicative behaviours and interaction quality as predictors of language development: findings from a community‐based study of slow‐to‐talk toddlers. Issue 2 (7th December 2017) - Conway, Laura J.; Levickis, Penny A.; Smith, Jodie; Mensah, Fiona; Wake, Melissa; Reilly, Sheena
Abstract: Background: Identifying risk and protective factors for language development informs interventions for children with developmental language disorder (DLD). Maternal responsive and intrusive communicative behaviours are associated with language development. Mother–child interaction quality may influence how children use these behaviours in language learning. Aims: To identify (1) communicative behaviours and interaction quality associated with language outcomes; (2) whether the association between a maternal intrusive behaviour (directive) and child language scores changed alongside a maternal responsive behaviour (expansion); and (3) whether interaction quality modified these associations. Methods & Procedures: Language skills were assessed at 24, 36 and 48 months in 197 community‐recruited children who were slow to talk at 18 months. Mothers and 24‐month‐olds were video‐recorded playing at home. Maternal praise, missed opportunities, and successful and unsuccessful directives (i.e., whether followed by the child) were coded during a 10‐min segment. Interaction quality was rated using a seven‐point fluency and connectedness (FC) scale, during a 5‐min segment. Linear regressions examined associations between these behaviours/rating and language scores. Interaction analysis and simple slopes explored effect modification by FC. Outcomes & Results: There was no evidence that missed opportunities or praise were associated with language scores. Higher rates of successful directives in the unadjusted model and unsuccessful directives in the adjusted model were associated with lower 24‐month‐old receptive language scores (e.g., unsuccessful directives effect size (ES) = −0.41). The association between unsuccessful directives and receptive language was weaker when adjusting for co‐occurring expansions (ES = −0.34). Both types of directives were associated with poorer receptive and expressive language scores in adjusted models at 36 and 48 months (e.g., unsuccessful directive and 48‐month receptive language, ES = −0.66). FC was positively associated with 24‐, 36‐ and 48‐month language scores in adjusted models (e.g., receptive language at 24 months, ES = 0.21, at 48 months, ES = 0.18). Interaction analysis showed the negative association between successful directives and 24‐month receptive language existed primarily in poorly connected dyads with low FC levels. Conclusions & Implications: These findings illustrate the effects of the combined interaction between different maternal communicative behaviours and features of the interaction itself on child language development, and the need to consider both in research and practice. Whilst more intrusive directives were associated with poorer language scores, this association attenuated when adjusting for co‐occurring responsive expansions, and the association was strongest for children in lower quality interactions. This work may inform clinical practice by helping clinicians target the most appropriate communicative behaviours for specific mother–child dyads.